Rūam kotmāi kīeokh̨ōng kap kānpatibat ngān kh̨ōng M̄ưang Phatthayā (Ngān Nitikān, K̨ōng Wichākān læ Ph̄ænngān, M̄ưang Phatthayā, 2003)
Compilation of administrative regulations of Pattaya Municipality, Central Thailand.